Chapter 3 Lunatics' rights activism in Britain and the German Empire, 1870-1920 a European perspective - Brückner, Burkhart (Social Histories of Medicine, 2021)
This comparative study examines the emergence and political significance of lunatics' rights activism in Europe between 1870 and 1920. In writing the history of the criticism of psychiatry, scholars have so far mainly focused on the second half of the twentieth century. This chapter, however, shows that the decades around 1900 already saw a widespread criticism 'from below' accompanying the professionalisation and modernisation of European psychiatry. The comparative analysis of the careers of two key campaign leaders, Louisa Lowe (1820-1901) in England and Adolf Glöklen (1861-c.1935) in Germany, reveals the similarities and differences in their motives, ways of campaigning, mobilisation success and political agency at the individual and collective level. Drawing on concepts from the political sociology of social movements and disability history, the chapter highlights the connections between early lunatics' rights activism and socio-historical categories like 'class', 'gender' and 'body' and identifies these campaigns as political predecessors of the contemporary consumer/survivor/ex-patient movement.